Особливості біохімічного складу плодів різних видів плодових рослин, інтродукованих на Південному Сході України. Повідомлення 2. Вміст цукрів - Mezhenskyj, V.M.; Mozhajeva, L.L.; Mezhenska, L.O. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2007)
The data about contents of sugars in fruits of 86 plants species from the gene pool collection of non traditional fruit crops of the National Centre for Plant Genetic Resources of Ukraine are given. The most contents of sugars in fruits of Elaeagnus angustifolia L. var. orientalis (L.) Ktze, E. argentea Pursh., E. multiflora Thunb., ×Louiserasus sp., Mespilus germanica L., Microcerasus tomentosa (Thunb.) Erem. et Yusсhev, ×Pyronia veitchii (Trabut) Guill., Shepherdia argentea (Pursh.) Nutt., Sorbus domestica L. was established.